Odnos prebivalcev obremenjenih območij do okolja in okoljskih problemov na vzorčnih primerih Šaleške doline in Zasavja - Šalej, Matjaž (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
In this article we focused attention on the inhabitants' response to the environmental problems in Šalek Valley and Zasavje Region. We used a questionnaire to survey the answers of 1395 inhabitants in both regions. The main aims of our study were following: to estimate the pollution severity and environmental conditions and to compare the answers between both. The inhabitants of the Šalek Valley are very critical toward their environment and they are basically satisfied with it (62,4 %). In the Zasavje Region the inhabitants are less satisfied (39,5 %) with their environment, because the pollution of their region is larger than average in Slovenia.
Keywords: Central Sava Valley; degradacija okolja; environmental protection; onesnaževanje okolja; regionalni razvoj; Slovenia; Slovenija; sonaravni razvoj; Šalek Valley; Šaleška dolina; varstvo okolja; Zasavje